Hedge Fund Activism, Corporate Governance, and Firm Performance - BRAV, ALON; JIANG, WEI; PARTNOY, FRANK; THOMAS, RANDALL (Journal of Finance, 2008)
ABSTRACT Using a large hand‐collected data set from 2001 to 2006, we find that activist hedge funds in the United States propose strategic, operational, and financial remedies and attain success or partial success in two‐thirds of the cases. Hedge funds seldom seek control and in most cases are nonconfrontational. The abnormal return around the announcement of activism is approximately 7%, with no reversal during the subsequent year. Target firms experience increases in payout, operating performance, and higher CEO turnover after activism. Our analysis provides important new evidence on the mechanisms and effects of informed shareholder monitoring.